The Influence of Parents' Economic Conditions and Learning Motivation on Students' Interest in Continuing Their Studies at Higher Education - Enjela Primiranda; Gusnardi Gusnardi; Hardisem Syabrus (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine the influence of parents' economic conditions and learning motivation on students' interest in continuing their studies to tertiary institutions in class XII students at SMK Nurul Falah Pekanbaru. The research population was all class XII students at SMK Nurul Falah Pekanbaru. The research sample was all students at SMK Nurul Falah Pekanbaru, totaling 43 students, with a sampling technique using a saturated sampling technique. The data collection method uses a questionnaire via Google Form, and the data collected is then tabulated and analyzed using multiple linear regression. Hypothesis testing is carried out using the F test and t test. Based on research results, the influence of parents' economic conditions and learning motivation has a positive and significant effect on students' interest in continuing their studies at university simultaneously or partially.